Constructing bifunctional nanoparticles for dual targeting: improved grafting and surface recognition assessment of multiple ligand nanoparticles. Issue 38 (16th September 2016) - Lo Giudice, Maria Cristina; Meder, Fabian; Polo, Ester; Thomas, Steffi S.; Alnahdi, Kholoud; Lara, Sandra; Dawson, Kenneth A.
Abstract : Simultaneous analysis of multiple ligands reveals new details in effective surface design of dual targeting nanoparticles. Abstract : Nanoparticles (NPs) functionalized with two active targeting ligands have been proposed in drug delivery for their promising capability to stimulate different pathways with one object. Due to the multivalency, the construction and analysis of the effective surface of such bifunctional nanoparticles, however, is significantly more complex than for nanoparticles bearing only one ligand. Here, we optimize construction and analysis of bifunctional NPs containing recognizable combinations of human serum albumin (HSA), transferrin (Tf), and epidermal growth factor (EGF) on fluorescent silica NPs grafted via common polyethylene glycol (PEG) linkers as a model system. Combined with an overall protein quantification, a mapping of exposed recognizable sequences using monoclonal antibodies conjugated to gold nanoparticles (AuNPs) or quantum dots (QDs) for enhanced spectroscopic and microscopic detection revealed that active protein sequences can be one to two orders of magnitude lower than overall conjugated proteins while possessing specific cellular recognition. In addition, we found that common conjugation strategies lead to a large excess of non-specifically compared to covalently bound ligands and instabilities that may impact targeting. These can be avoided by certain synthetic conditions presented here for effective exploitation of multivalent surfaces in nanomedicine.